NEW CONSTITUTION: DESIGNATION OF UZBEKISTAN AS A SOCIAL STATE - Shirinova Nilufar (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The designation of the Republic of Uzbekistan as a social state in the new constitution of the Republic of Uzbekistan through clarifying statements are given in the article.